ANALISI YURIDIS TENTANG TAKHARUJ (KELUAR) DALAM MENERIMA BAGIAN WARISAN DAN AKIBAT HUKUNYA MENURUT FIKIH ISLAM (STUDI KASUS DIKECAMATAN LAMPRIT KOTA BANDA ACEH) - MAULIDA KARYANTI (PREMISE LAW JURNAL, 2015)
The result of the research showed that the factor which caused heirs to withdraw was that he loved the other destitute heirs and wanted to help them. In the Islamic fiqh (laws dealing with ritual obligation), it is allowable when it is done voluntarily as it is stipulated in Article 183 of the Compilation of the Islamic Law which states that “the heirs agree to reconcile in the distribution of the inheritance after each of them kows his own share.” The status of the inheritance of the heir who has withdrawn becomes the share of those who do not withdraw. The legal consequence is that a heir cannot withraw before there is the reconciliation among all heirs according to Article 183 of the Compilation of the Islamic Law. Keywords: Takharuj (Withdrawal), Iheritance, Islamic Fiqh